2019
DOI: 10.1039/c9cp03211h
|View full text |Cite
|
Sign up to set email alerts
|

Statistically representative databases for density functional theoryviadata science

Abstract: Cluster analysis applied to quantum chemistry: a new broad database of chemical properties with a reasonable computational cost.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
3

Relationship

5
4

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 173 publications
0
32
0
Order By: Relevance
“…This clearly reflects the stabilizing effect of an acyl radical in the transition state of the 1,6-migration. Therefore, based on the expected accuracy of our calculations (~±0.5 kcal/mol), [58][59][60][61][62] we can conclude that the reaction does not proceed through the cyclic structure (9) neither in the triplet nor in the singlet state. Using the same computational strategy, we found that the modification of the substitution pattern on 7-nitroindoline is not as important as initially thought.…”
Section: Figurementioning
confidence: 52%
“…This clearly reflects the stabilizing effect of an acyl radical in the transition state of the 1,6-migration. Therefore, based on the expected accuracy of our calculations (~±0.5 kcal/mol), [58][59][60][61][62] we can conclude that the reaction does not proceed through the cyclic structure (9) neither in the triplet nor in the singlet state. Using the same computational strategy, we found that the modification of the substitution pattern on 7-nitroindoline is not as important as initially thought.…”
Section: Figurementioning
confidence: 52%
“…This reflects the stabilizing effect of an acyl radical in the transition state of the 1,6-migration. The energy difference between the migration and the cyclization pathways is calculated at 1.1 kcal/mol, and since the expected accuracy of our calculations is ±1.0 kcal/mol,50,[65][66][67][68] we can conclude that the two mechanisms are competitive. As such, given the small activation barriers, both mechanisms can co-occur.…”
mentioning
confidence: 51%
“…Instead, one may use statistical methods for the partitioning of the full set. Indeed, this approach has been adopted in a recent study, in which a large dataset of ~7000 points is grouped into 16 “clusters.” [ 76 ] In a similar manner, we apply the standard statistical clustering technique for the CUAGAU‐2 dataset. Specifically, the data points are clustered according to the deviations from benchmark values for all assessed methods.…”
Section: Resultsmentioning
confidence: 99%